Survivable Traumatic Thoracic Aortic Transection After Pedestrian–Vehicle Collision: A Case Report - SULTANOĞLU, Hasan; BİRLİK, Enes Malik; KÖSESOY, Muhammed Enes (Brazilian Journal of Case Reports, 2026)
Traumatic thoracic aortic transection is a rare but highly lethal consequence of high-energy blunt trauma, and early diagnosis is essential for survival. A 56-year-old male was brought to the emergency department after a high-energy pedestrian–vehicle collision. He was conscious and hemodynamically stable on arrival but had chest pain, dyspnea, thoracic tenderness, decreased breath sounds over both hemithoraces, and left upper quadrant abdominal tenderness. Initial portable chest radiography showed mediastinal widening and heterogeneous opacity in the left lower lung zone. Because of the trauma mechanism and suspicion of multisystem injury, contrast-enhanced thoracoabdominal computed tomography angiography was performed. Imaging demonstrated focal disruption of the aortic wall at the distal aortic arch–proximal descending thoracic aorta junction, with a 30 × 20 × 28 mm pseudoaneurysm and para-aortic mediastinal hematoma causing rightward displacement of the trachea. Additional injuries included suspected pulmonary contusion/laceration, small bilateral high-attenuation pleural effusions, fractures, and suspected splenic laceration. The patient underwent urgent definitive aortic repair and was discharged in good clinical condition on the seventh hospital day. This case emphasizes the value of early computed tomography angiography in survivable blunt multitrauma with suspected major vascular injury.